IMPLEMENTASI KEBIJAKAN PEMBERIAN BANTUAN PERBAIKAN RUMAH MASYARAKAT PASCA BENCANA DI KABUPATEN KEBUMEN - , Joko Fitra, Dr. Luthfi Mutaâali, MSP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research examine about the implementation of housing repair assistance in the period of post disaster. Kebumen District Local Government can not asking assistance from the Central Government or from Provincial Government because of requirements that has been set up by BNPB. On the other hand, the Local Government ability still can not comply with the regulation that has been issued by the BNPB. This research is aimed to examine the results and impact of giving assistance and also to determine the influencing factors. The approach of this study using qualitative descriptive. Collection data technique using observation, semi structure interview, and documentation study. The subject of this research is chosen with purposive approach. Data analysis using Miles and Huberman Model which consist of collecting data, reduction data, serving data and conclusion. The results of this research show that kebumen district has high potential housing damage. The ability of Kebumen District in giving assistance to repair house in the period of post disaster still in low level, where the local government only help 16.73 % from the total damaged house and 2.91 % from total lost. Housing repair assistance involved private and business sector, such as BAZDA Kebumen district and IWAKK Lawet Mas. The impacts of housing repair assistance are :1) reconstruction of housing on high class community, 2) the increasing of community solidarity 3) reconstruction of housing failed in low class community, 4) the a rising of social gap. Finally, the implementation of housing repair assistance is successful due to efficient, and good response even though itâs not effective and less transparent. The success of giving housing repair assistance in the period of post disaster in Kebumen District was influenced by the communication between implementer and disaster victim, a good disposition, the implementor characteristic who care with disaster victims, and also there is no fraction in the implementor body. The limitation of resources is the main factor contributes to the ineffectiveness of housing repair assistance policy, but on the other hand, it can stimulate the implementer make a good breakthrough in order to achieve the objective of policy. The breakthrough that has been implemented was searching another resources fund and searching bailout for disaster victim.